Efficaciora Aditus: The Lived Experiences of Social Studies Teachers in Teaching Emerging Issues - Anne G. Cimatu, Rocel (Researchparks Publishing, 2025)
In the Philippine K–12 curriculum context, Social Studies teachers are increasingly tasked with addressing emerging issues such as gender identity, socio-political conflicts, and environmental crises to develop students' critical thinking and civic engagement. Despite integrating Kontemporaryong Isyu into the Grade 10 curriculum, many teachers face significant challenges due to outdated and limited resources, lack of student interest, and the sensitive nature of these topics. This study explored the lived experiences of Social Studies teachers in teaching emerging issues in selected public high schools in Santa Rosa, Laguna, focusing on their challenges and effective approaches. In-depth semi-structured interviews were conducted with ten Grade 10 Social Studies teachers using a qualitative research design grounded in transcendental phenomenology. Thematic analysis, guided by Colaizzi’s framework, revealed challenges such as student discomfort and disengagement, instructional difficulties, and external factors affecting learning. However, participants highlighted effective approaches, including active and interactive methods, encouraged critical thinking, practiced ethical and inclusive teaching, managed discussions effectively, and continuously adapted through professional growth. Anchored on the Social Representations Theory and Freire’s Critical Pedagogy, the study underscored the need for capacity-building programs to equip teachers with the skills to navigate complex classroom conversations. Findings contribute to educational policy and teacher training, advocating for learner-centered approaches that make classroom discussions of emerging issues inclusive, critical, and transformative. Ultimately, the research emphasizes Social Studies educators' vital role in fostering informed, empathetic, and socially responsible citizens.